Studi Fenomenologi Tentang Behavior Pattern Mahasiswa Akuntansi: Serupa atau Tak Samakah? - Ayu Puspitasari; Rafles Ginting; Wukuf Dilvan Rafa (Universitas Kristen Maranatha, 2023)
The COVID-19 pandemic has significantly altered the order of human life. One of the aspects affected by the COVID-19 pandemic is education. The original face-to-face learning system has been converted to a distance learning system (online) as a result of the implementation of Large-Scale Social Restrictions (PSBB) to encourage people to avoid crowds. This pandemic period, however, has passed, and Indonesia was declared endemic by the Coordinating Minister for the Economy at the end of December 2022. As a result, Indonesia is said to have entered a new normal era in which human life has returned to pre-pandemic levels while adhering to health protocols. The goal of this research is to look at how students' lifestyles changed after the COVID-19 pandemic ended, as well as the potential for changes in Accounting students' behavior patterns. This study investigates and explains the behavioral changes of Accounting students at the Faculty of Economics and Business, University of Tanjungpura, during the COVID-19 pandemic (FEB UNTAN). This is a qualitative study that takes a phenomenological approach. In this study, data was collected through observation and in-depth interviews with several students from the Bachelor of Accounting Study Program (informants). According to the findings of this study, accounting students experienced changes in their behavior patterns and life orientation following the pandemic. Students become more involved in various organizational activities on and off campus, and they are more motivated to learn and achieve their goals.Keywords: Accounting Student, Behavior, COVID-19 Pandemi